Spatial autocorrelation of communes websites: A case study of the region Stredné Považie in Slovakia - Klobučník Michal; Bačík Vladimír (Bulletin of Geography. Socio-Economic Series)
Since its origination the Internet has been the basic communication channel through which e-Government processes in our society are carried out. The basic element of such processes is an existing website. This paper is the result of long-term research during which the authors collected information on the presence or absence of websites of self-governments in Slovakia. The output can be divided into two main parts. The first one, on the basis of the acquired data, evaluates the overall trend of self-government websites between 2008-2012. The results were distributed in the form of a website devoted to communes of Slovakia, using technology enabling the graphical and cartographic interpretation of the results. In the second part, on the basis of the gathered data, the authors applied spatial autocorrelation, specifically the ‘join count statistics’ method with the subsequent application to selected phenomenon in society, in particular the occurrence of websites of a selected region of Stredné Považie in Slovakia at the same time interval. This way the authors wanted to point out the interaction of communes in the development of websites, whether through inspiration or rivalry among neighbouring communes. From this point of view, mainly in the first period under review (2008), positive spatial autocorrelation is apparent in the occurrence of communes with websites.